2017
DOI: 10.1007/s00442-017-3953-x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and antioxidant defense associate with parasite-induced retarded growth in wild brown trout

Abstract: Early growth conditions can have profound impacts on individuals' development, growth and physiology, with subsequent long-term consequences for individuals' fitness and life expectancy. Telomere length (TL) has been suggested to indicate both individual fitness and life expectancy in wide range of species, as the telomere attrition rate at early age can be accelerated due to exposure to various stressors, including parasites and inflammatory diseases, which increase production of reactive oxygen species (ROS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 93 publications
4
16
0
Order By: Relevance
“…Uninfected males showed intermediate TL between the ones infected with Plasmodium and Haemoproteus . This lack of effect has already been reported in other animals (Slowinski 2017; Stauffer et al 2017) and adds to the evidence that parasitic infections do not always entail negative consequences on TL. In general, the information on the relationship between telomere dynamics and parasitic infections is still lacking, and comparisons among taxa have to be treated with great caution since telomere dynamics and telomerase activity varies substantially within animal kingdom (Olsson et al 2018).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Uninfected males showed intermediate TL between the ones infected with Plasmodium and Haemoproteus . This lack of effect has already been reported in other animals (Slowinski 2017; Stauffer et al 2017) and adds to the evidence that parasitic infections do not always entail negative consequences on TL. In general, the information on the relationship between telomere dynamics and parasitic infections is still lacking, and comparisons among taxa have to be treated with great caution since telomere dynamics and telomerase activity varies substantially within animal kingdom (Olsson et al 2018).…”
Section: Discussionsupporting
confidence: 79%
“…This study suggests that disease-induced negative effects on survival may be mediated through telomere degradation. Other studies also report negative effect of parasitic infections on TL in siskins and tawny owls (Asghar et al 2016; Karell et al 2017), however some recent studies failed to show such relationship (Slowinski 2017; Stauffer et al 2017). This inspires further query on assessing telomere dynamics in various populations in response to parasite-induced diseases.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, TIN2 has been shown to insure cell viability independently of any telomere length regulation [60], underlying that its expression may also participate in the mitigation of negative side effects of inflammation. Previous studies suggested that telomere length is involved in the capacity of individuals to respond to infection [61,62]. Based on our data, we hypothesize here, using a proteomic exploratory approach, that the age-related costs of the innate response to LPS imply at least partly a telomere and/or telomerase-related pathway.…”
Section: Discussionsupporting
confidence: 60%
“…Accordingly, individuals exhibiting tolerance to parasites should also demonstrate lower telomere shortening rates and have longer telomeres in comparison with individuals that apply immune responses for to fighting off parasites. In line with this hypothesis, in a natural population of juvenile brown trout (Salmo trutta), individuals that were less sensitive to parasite-induced impaired growth (and therefore demonstrated higher tolerance) showed longer telomeres [28]. We therefore predict that host phenotypes that demonstrate higher levels of tolerance also show reduced telomere attrition rates during the infection when compared with host phenotypes that are more prone to fight off the parasites (higher resistance phenotypes), and suggest that host telomere attrition rate should be an important trait to analyse in future studies of disease tolerance in the wild.…”
Section: Living In the Real World: Tolerance Resistance And Co-infecmentioning
confidence: 80%